High‐resolution measurements of microphysics and entrainment in marine stratocumulus clouds - Yeom, Jae Min; Szodry, Kai‐Erik; Siebert, Holger; Ehrlich, André; Mellado, Juan Pedro; Shaw, Raymond A.; Yum, Seong Soo (Quarterly journal of the Royal Meteorological Society, 2024)
High‐resolution measurements from the Airborne Cloud‐Turbulence Observation System (ACTOS) during the Azores Stratocumulus Measurements of Radiation, Turbulence and Aerosols (ACORES) campaign are analysed for an investigation of the vertical profiles of microphysical properties and entrainment velocity (We) in marine stratocumulus clouds. The vertical profiles show the transition from the cloudy layer to free troposphere with nearly linear profiles of total water mixing ratio, liquid water potential temperature and virtual potential temperature, but the thickness of entrainment interfacial layer varies significantly. Sharp transitions of cloud microphysical and optical properties within a single horizontal flight leg are found in one stratocumulus cloud system. They seem to be related to the local environmental conditions, such as the wind shear and turbulent dissipation rate. We values estimated by three methods show consistent tendencies in general and are clearly related to the local environmental conditions, such as vertical shear of the horizontal wind and turbulence intensity. However, the magnitudes of We values differ by up to two orders of magnitude depending on the methods, which suggests that the estimation of We from in situ measurements is still a challenge. Analysis of the microphysical response to entrainment suggests that inhomogeneous mixing occurs dominantly. On the other hand, the analysis results for the clouds under more humid conditions indicate a higher likelihood of homogeneous mixing. The estimation of entrainment velocity has been the subject of sustained scientific effort, and a large number of approaches have been developed. Entrainment velocity values estimated by three methods show consistent tendencies and are related to the local environmental conditions. However, the magnitudes of entrainment velocity values differ by up to two orders of magnitude depending on the methods, which suggests that the estimation of entrainment velocity from in situ measurements is still a challenge.